PROMOTING LEARNING THROUGH JOURNAL WRITING - Made Frida Yulia (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
Journals have received an increased interest in education context. They have been found to be a fruitful way of communication between teacher and students. Liuolienė & Metiūnienė (2009) mention some purposes of journal writing. It can create a positive atmosphere for learning and foster deep learning by making learners relate new knowledge with the previous one. Moreover, as confirmed by Boud (2001), journal writing encourages students to articulate their level of understanding. It is part of reflective learning and a tool to facilitate language skill development. Through this activity learners are shaped to become reflective, which is crucial for their learning advancement. The study aimed at describing the effects of journal writing on ELESP students in three courses from different semesters. They were Structure I, Textual Pronunciation, and Micro Teaching classes. The sources of the data were the students’ reflective writings. From the analysis it was discovered that the students gained benefits from the use of journal writing in their classes. They showed that they became reflective learners, who could make meaning of what they learned. They were also trained to be more critical of their own ability, and hence were more able to find ways to advance. By so doing, their autonomy in learning was developed.